Nilai – Nilai Tradisi Turun Tanah Perspektif Masyarakat Di Desa Pangkalan Nyirih Kecamatan Rupat Kabupaten Bengkalis - Rizky Firnando; Siti Zahara (Al-Amin: Jurnal Ilmu Pendidikan dan Sosial Humaniora, 2023)
This article discusses the values of inherited traditions from the perspective of the people in Pangkalan Nyirih Village, Rupat. This tradition is one of the customs that is still adhered to and preserved from generation to generation by the people of the village. This study used a qualitative descriptive method using data collection techniques in the form of interviews, observation, and documentation. The results of the study show that the tradition of descending to the ground is carried out by children aged 7-9 months or more to introduce them to nature (land) as a foothold. In addition, this tradition also contains a religious meaning which teaches that humans were created from soil and will return to it. In this tradition there are values such as hospitality, religious, and social. These values strengthen brotherhood, ask God for blessings and health, and promote cooperation and mutual cooperation in society. This article concludes that the tradition of descending from the ground has important values in shaping cultural identity and strengthening social relations in the people of Pangkalan Nyirih Village. The advice given is the need to maintain and preserve this tradition so that it can continue to be a valuable part of the cultural heritage of the local community